EFFECT OF ACID TYPE AND PARTICLE SIZE ON THE YIELD AND PURITY OF APPLE (MALUS DOMESTICA ‘FĂLTICENI’) POMACE PECTIN - Florina DRANCA (Stefan cel Mare University of Suceava, 2018)
This work proposes the use of Malus domestica ‘Fălticeni’ pomace, resulted from the processing of apples into juice in the geographical area of Fălticeni, Suceava (Romania), as a source for pectin extraction. Pectin was extracted from this plant source by using two extractants - hydrochloric acid and citric acid, separately at pH 2, solid-to-liquid ratio of 1:20, temperature of 90°C, and extraction time of 120 min. Together with acid type, another variable that was varied was the particle size: 200-300 µm, 125-200 µm, and <125 µm. To study the influence of acid type and particle size, pectin was characterized in terms of yield and purity, expressed as uronic acid content. The results showed that acid type and particle size had significant effects on the pectin yield and its uronic acid content. A strong influence of acid type on the extraction yield was recorded by particle sizes of 200-300 µm and 125-200 µm, respectively. Regarding the uronic acid content, it was observed that particle sizes of 200-300 µm determined a good purity of the extracted pectin, independent of acid type, while for particle sizes of 125-200 µm and <125 µm, the uronic acid content of pectin was strongly affected by the acid used. The highest pectin yield (21.24%) and uronic acid content (93.90 g/100g) were obtained for citric acid extraction and particle sizes between 125 and 200 µm.